Methodology for Designing a Gastronomic Route in the District of Pachacamac - Pizarro-Ramos, Pedro L. (2024)
The study was conducted in the district of Pachacamac, a destination recognized for its significance in offering a variety of dishes from the three regions of the national territory. The establishment that served as the pilot to generate the Methodology for designing a Gastronomic Route was selected through a series of criteria that evaluated different aspects of the restaurant, supported by López et al. (2022). To identify the characteristics of the visitor, an 11-question closed questionnaire in Office Forms was used, validated by three specialists, administered in 4 sessions each weekend, and analyzed with IBM SPSS Statistics. The survey was conducted in the Plaza de Armas of the District of Pachacamac during the gastronomic fairs held every weekend. The sample included 383 people and focused on demographic, psychographic, and behavioral aspects. The results revealed that proposing a methodology to design a gastronomic route in the district of Pachacamac involves designing a route that integrates cultural or natural heritage, allowing participants to discover and enjoy the culinary offerings of this district. From this, it is inferred that it is important to consider analysis, selection of points of interest, route design, partnerships, promotional material, pilot testing, monitoring, and mapping.